Histological and immunohistochemical evaluation of the effect of local exogenous application of VEGF on bone healing (experimental study in rat) - Fadhil, Enas; Alhijazi, Athraa Y (Journal of Baghdad College of Dentistry, 2014)
Background: The repair of bone defects remains a major clinical orthopaedic challenge. Bone is a highly vascularised tissue reliant on the close spatial and temporal connection between blood vessels and bone cells to maintain skeletal integrity. Angiogenesis thus plays a pivotal role in skeletal development and bone fracture repair. The role of angiogenic and osteogenic factors in the adaptive response and interaction of osteoblasts and endothelial cells during the multi step process of bone development and repair will be highlighted in this study. This study aimed to identify the role of local exogenous vascular endothelial growth factor in bone healing and to analyze the expression of VEGF by immunohistochemistry in created bone defect after application with different biomaterials in a rat model. Materials and methods: In this experimental study eighteen male Albino rats, weighing (300-400) gram, aged (6-8) months were used and maintained under control conditions of temperature, drinking and food consumption. The animals were subjected for a surgical operation of medial sides of both tibiae bone ( right side was considered as experimental site ,while left be the control one), in control group the bone defect treated with local application of 1Âµm of normal saline, while experimental treated with local application of 1Âµm of VEGF .The rats were sacrificed at 3,7,10 days after surgery(six rats for each period). Bone healing was histologically examined with immunohistochemical localization of VEGF Results: Bone defect treated with local application of VEGF shows an early osteoid tissue deposition with high cell count for osteoblast, osteocyte and osteoclast. Immunohistochemical evaluation for VEGF by stromal cells, reported to be higher with significant difference in VEGF group in comparison to control. Conclusion: The study illustrated that low application of VEGF could be an effective therapeutic expression for bone injuries; these data are promising for a possible future clinical usage.